Analysis of Website Quality Influence ppta.stikom.edu Against User Satisfaction Based on Method of Webqual 4.0 - Erlangga, Ryan gusti; Sunarto, Dewiyani; Tjandrarini, Asteria B. (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
As an actor in the world of education, it is very important for the Institute of Business and Informatics Stikom Surabaya to continuously strive in providing maximum service for its students. One of the facilities provided by the campus is providing the website ppta.stikom.edu. The website has the main function of searching the title of the final task that already exists, search mentors, and see the schedule of the final hearing. Since the website of Pusat Pelayanan Tugas Akhir (PPTA) was launched, the website manager never did a process of quality analysis of his website. Website quality is an important factor to increase the interest of students to visit the website. Therefore, the quality analysis of PPTA website is very necessary. According (Sanjaya, 2012) WebQual 4.0 is one method or technique of measuring website quality based on end user perception. WebQual 4.0 consists of 3 dimensions: usability, information quality, and interaction services . The results of the analysis can be recommended for the PPTA in developing a quality website, so that the development of PPTA website can increase to the maturation level, stabilization, and ultimately reach the level of utilization.